Front bilobed encephalocele - Dávila Aliaga, Carmen Rosa (2020)
The frontal encephalocele represents a rare congenital anomaly of the anterior neuroporous closure, with herniation of the cranial content. We present the clinical case of a newborn born at the Maternal Perinatal Institute, who presented at birth, a frontal bilobed encephalocele, without associated commitment, even in our setting we lack multidisciplinary management guidelines that allow a favorable prognosis and evolution.